An Analysis of the Impact of the Development of the Sungai Biru Tourism Village on Community Income and Well-being from an Islamic Economics Perspective - Preti Sinta; Melia Frastuti; Waldi Nopriansyah; Nur Fatahiah Abd Razak (Universitas Indo Global Mandiri, 2026)
Sungai Biru Tourism Village in Pali Regency is one of the emerging tourist destinations that provides economic opportunities for the local community. The development of this tourism area has encouraged the growth of various business activities that contribute to improving community welfare. From the perspective of Islamic economics, welfare is not solely measured by increased income but also by the realization of public benefit, justice, and sustainability in economic activities. This study aims to examine the effect of the development of Sungai Biru Tourism Village on community economic welfare from an Islamic economic perspective. This study employed a quantitative approach. Data were collected through questionnaires, interviews, and documentation. The respondents consisted of tourism managers, local business owners, and visitors involved in tourism activities. The collected data were analyzed using statistical methods to determine the relationship between tourism village development and community economic welfare.The results indicate that the development of Sungai Biru Tourism Village has a positive and significant effect on community economic welfare. Tourism activities have created new business opportunities, expanded employment opportunities, and increased community income. Furthermore, community participation in tourism management reflects the implementation of Islamic economic values that emphasize justice, public benefit, and equitable distribution of economic gains. Therefore, the development of Sungai Biru Tourism Village can serve as an alternative strategy for sustainable community economic empowerment. Keywords: Tourism Village, Economic Welfare, Islamic Economics.